The comparative cycle in crosslinguistic perspective - Agnes Jäger (Linguistic Typology at the Crossroads, 2021)
This paper traces the diachronic development of comparison constructions crosslinguistically, highlighting a recurrent pattern of change with respect to standard markers: the comparative cycle. Using diachronic corpus data as well as data from descriptive grammars and handbooks, it is demonstrated that comparison particles and other standard markers in many languages undergo a syntactic-semantic distributional shift from marking equality to marking inequality. More specifically, we witness a stepwise and recurrent – i.e. cyclical – shift of standard markers from similatives to equatives and to comparatives. The comparative cycle is compared to other instances of cyclical change and linked to linguistic economy and the markedness hierarchy of comparison constructions.